Diagnosis of small bowel Crohn's disease: a prospective comparison of capsule endoscopy with magnetic resonance imaging and fluoroscopic enteroclysis. Issue 12 (14th July 2005) - Albert, J G; Martiny, F; Krummenerl, A; Stock, K; Leßke, J; Göbel, C M; Lotterer, E; Nietsch, H H; Behrmann, C; Fleig, W E
Abstract : Background and aims: The diagnostic yield of capsule endoscopy (CE) compared with magnetic resonance imaging (MRI) in small bowel Crohn's disease is not well established. We prospectively investigated CE, MRI, and double contrast fluoroscopy in patients with suspected small bowel Crohn's disease. Methods: Fifty two consecutive patients (39 females, 13 males) were investigated by MRI, fluoroscopy and—if bowel obstruction could be excluded—by CE. In 25, Crohn's disease was newly suspected while the diagnosis of Crohn's disease (non-small bowel) had been previously established in 27. Results: Small bowel Crohn's disease was diagnosed in 41 of 52 patients (79%). CE was not accomplished in 14 patients due to bowel strictures. Of the remaining 27 patients, CE, MRI, and fluoroscopy detected small bowel Crohn's disease in 25 (93%), 21 (78%), and 7 (of 21; 33%) cases, respectively. CE was the only diagnostic tool in four patients. CE was slightly more sensitive than MRI (12 v 10 of 13 in suspected Crohn's disease and 13 v 11 of 14 in established Crohn's disease). MRI detected inflammatory conglomerates and enteric fistulae in three and two cases, respectively. Conclusion: CE and MRI are complementary methods for diagnosing small bowel Crohn's disease. CE is capable of detecting limited mucosal lesions that may be missed by MRI, but awareness of bowel obstruction is mandatory. In contrast, MRI is helpful in identifying transmural Crohn's disease and extraluminal lesions, and may exclude strictures.